Carcinosarcoma of submandibular salivary gland: our experience of a rare tumour with review of literature - Pancholi, Mayank; Desai, Sanjay M.; Pancholi, Anuradha (International Surgery Journal, 2016)
Carcinosarcoma arising from the submandibular gland is a very rare pathologic entity. Rarity of tumour makes the treatment recommendations difficult. We share our experience of a 76 year old gentleman who presented with a swelling in right submandibular region which was present since last fifteen years and increased over last one month. Fine needle aspiration cytology was done preoperatively which was suggestive of salivary gland carcinoma. After investigating properly a diagnosis of malignant tumour arising from submandibular gland was made and he underwent submandibular gland fossa clearance with ipsilateral modified radical neck dissection. Post-operative histopathology with immunohistochemistry correlation was suggestive of carcinosarcoma arising from pre-existing pleomorphic adenoma of submandibular gland. He received radiotherapy as adjuvant treatment.